+0  
 
0
126
1
avatar+131 

-14=2(h-3)

            5

xRainexSiderisx  Mar 7, 2017

Best Answer 

 #1
avatar+4155 
+11

\(-14=\frac{2(h-3)}{5}\)

 

Multiply both sides of the equation by 5:

\(-14(5)=2(h-3) \\~\\ -70=2(h-3)\)

 

Divide both sides of the equation by 2:

\(\frac{-70}{2}=(h-3) \\~\\ -35=h-3\)

 

Add 3 to both side of the equation:

\(-35+3=h \\~\\ -32=h\)

hectictar  Mar 7, 2017
Sort: 

1+0 Answers

 #1
avatar+4155 
+11
Best Answer

\(-14=\frac{2(h-3)}{5}\)

 

Multiply both sides of the equation by 5:

\(-14(5)=2(h-3) \\~\\ -70=2(h-3)\)

 

Divide both sides of the equation by 2:

\(\frac{-70}{2}=(h-3) \\~\\ -35=h-3\)

 

Add 3 to both side of the equation:

\(-35+3=h \\~\\ -32=h\)

hectictar  Mar 7, 2017

5 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details